DEVELOPMENT OF WORD CLASSES DIGITAL LEARNING MEDIA FOR SYNTAX COURSE - M. Ridho Kholid; Meisuri; Agus Hidayat (Jurnal Scientia, 2022)
This research aims to develop a digital word class learning media to be used in English Syntax subjects and to determine the feasibility of the developed learning media to support English Syntax learning. In this R & D research, the researchers employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The researchers investigated the product's feasibility by performing small-scale and large-scale trials. The research findings indicate that the developed media was practical and useful. In short, the developed media is feasible to assist students in learning word classes to support syntax learning.